PENALIZED GENERALIZED FISCHER-BURMEISTER FUNCTION FOR SOCCP - Kum, Sangho; Lim, Yongdo (Taiwanese journal of mathematics, 2011)
Recently, Pan et al. [11] developed the merit function method for SOCCP based on the generalized Fischer-Burmeister (FB) function. This note is along the same line. Indeed, we study a penalized version of the generalized FB function and provide a basic theoretical property that the level set of the merit function induced by the penalized version of the generalized FB function is bounded under suitable assumptions. The proof relies on trace inequalities. 2010Mathematics Subject Classification:Primary 90C25, 65K05. Key words and phrases: Complementarity problem, Complementarity functions, Merit functions, Symmetric cones, Second-order cone, Fischer-Burmeister function.